Application of Technology-Based IRE Learning Methods to Increase Student Learning Motivation - Thabranie, Abdul Qayyum; Syawarnih, Nur; Mardina, Dina (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study analyzes the implementation of technology-based Islamic Religious Education (IRE) and its specific impact on student learning motivation at Al Ihsan Berau Junior High School. Employing a qualitative descriptive approach with data from observations, interviews, and documentation, this research moves beyond descriptive narratives to examine the mechanisms of student engagement. The findings reveal that technology enhances motivation through a dual-pathway mechanism: (1) the cognitive pathway, where multimedia design (following CTML principles) reduces cognitive load and sharpens focus; and (2) the emotional pathway, where interactive features satisfy students' psychological needs for competence and autonomy (aligning with Self-Determination Theory). Critically, however, the study finds that while digital engagement significantly boosts intrinsic motivation and cognitive understanding, it is less effective in internalizing religious values without teacher-led mentorship. Theoretically, this research contributes a conceptual framework integrating CTML and SDT within the context of Islamic education. Practically, it offers an inclusive “offline-first” strategy to mitigate digital divide challenges in suburban schools, ensuring that technological adoption enhances motivation equitably without compromising the depth of moral education.